The Effect of ethanol extract of Kaffir lime leaves on Lipid Profile, Aterogenetic Index and Blood Vessel Histopathology of Male White Rats Hyperlipidemia Model - Apriza, Reni; Siahaan, Jekson Martiar; Julianto, Endy; Ilyas, Syafruddin; Tarigan, Menang Bastanta (International Journal of Computational and Experimental Science and Engineering, 2025)
Kaffir lime leaf extract has the potential to be used as an antioxidant and anti-inflammatory, apart from that, the compounds contained in kaffir lime leaves have properties that can be used as medicine. This study used a laboratory experimental design on male white Wistar hyperlipidemic rats. The research method uses a post-test only controlled group design. Hypercholesterolemia induction uses a high-fat feed method, this feed contains quail egg yolk, duck egg yolk, 3 mL/300 mg/kgBW/day of used cooking oil. The statistical tests used are data normality and homogeneity tests. The results of phytochemical screening on kaffir lime leaves showed secondary metabolites such as flavonoids, phenols, saponins, tannins and alkaloids. In this study there was a significant difference in mean body weight (p<0.05) on the 14th day but there was no difference between groups on the 21st day. Apart from that, there were no significant differences in mean levels of total cholesterol, triglycerides, HDL (High-density lipoprotein), and LDL (Low-Density Lipoprotein) (p<0.05) between all groups. In eNOS levels there were no significant differences (p<0.05) between all groups. However, in HMGCOA levels, there were significant differences in levels (p<0.05) between all groups. Apart from that, the group with the ethanol extract of kaffir lime leaves at a dose of 35 mg/kgBW was better at controlling body weight, reducing total cholesterol, HDL, LDL and triglyceride levels, increasing eNOS levels and reducing HMGCOA levels.